Provenance of the Middle Siwalik sandstones of the Himalayan foreland basin (south central Kumaun, India): Implications for tectonics and paleoclimate of the source area. (27th January 2019) - Goswami, Pradeep K.
Abstract : Thirty medium‐ to fine‐grained sandstone samples of the Middle Siwalik Subgroup of the south central Kumaun Himalaya have been subjected to detailed petrographic and petrofacies analyses. The sandstones are moderately to well‐sorted, lithic and sublithic arenites. They are quartzolithic, having abundance of metasedimentary and sedimentary lithic fragments, which characteristically derive from a recycled, collision orogen provenance of quartzose and mixed quartzose‐lithic terrains. The primary and accessory framework grains of the sandstones are of mixed igneous, sedimentary, and low‐ to high‐grade metamorphic affinity. The petrographic and petrofacies characters suggest derivation of the sandstones from a vast area extending across the nearby located Lesser and Great Himalayan terrains. A comparison of these sandstones' QtFL petrofacies and petrographic characters with the similar data from Middle Siwalik sandstones of other studied sections reveals that their compositions are comparable all across the entire expanse from Potwar Plateau in Pakistan to eastern Himalaya in India; the Middle Siwalik sandstones everywhere have been sourced from the Lesser and Great Himalayan terrains, albeit with varying proportions through space and time.